2015
DOI: 10.1007/s12264-014-1491-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in gray matter volume correlate with catechol-O-methyl transferase gene Val158Met polymorphism in first-episode treatment-naïve patients with schizophrenia

Abstract: The catechol-O-methyltransferase (COMT) gene is a schizophrenia susceptibility gene. A common functional polymorphism of this gene, Val158/158Met, has been proposed to infl uence gray matter volume (GMV). However, the effects of this polymorphism on cortical thickness/ surface area in schizophrenic patients are less clear.In this study, we explored the relationship between the Val158Met polymorphism of the COMT gene and the GMV/ cortical thickness/cortical surface area in 150 firstepisode treatment-naïve patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Electrophysiological studies have also shown that the visual cortical response to stimulation at higher spatial frequencies is reduced in anisometropic amblyopia [11]. Global brain gray matter [12], including the visual cortex [13], has been investigated physiologically and psychopathologically using functional magnetic resonance imaging (fMRI). Furthermore, recent fMRI studies have shown that amblyopia is associated with deactivation in the striate cortex (Brodmann area 17), the occipitotemporal cortex, and the LGN [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological studies have also shown that the visual cortical response to stimulation at higher spatial frequencies is reduced in anisometropic amblyopia [11]. Global brain gray matter [12], including the visual cortex [13], has been investigated physiologically and psychopathologically using functional magnetic resonance imaging (fMRI). Furthermore, recent fMRI studies have shown that amblyopia is associated with deactivation in the striate cortex (Brodmann area 17), the occipitotemporal cortex, and the LGN [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…These previous findings converge to indicate that the reciprocal interactions between COMT genotype, dopamine levels, and structural and/or functional alterations in the human brain are related to mental disorder symptoms, such as AVHs (Lu et al., 2007; Kang et al., 2010; Sagud et al., 2010; Gothelf et al., 2011; Edgar et al., 2012; Tian et al., 2013a,b; Li et al., 2015; Huang et al., 2016; Steiner et al., 2018). …”
Section: Introductionmentioning
confidence: 99%
“…The catechol-o-methyltransferase ( COMT ) genotype influences brain functional (including auditory processing, which is highly related to AVHs) and dopaminergic alterations both in healthy people and in patients with schizophrenia ( Lu et al., 2007 ; Kang et al., 2010 ; Gothelf et al., 2011 ; Edgar et al., 2012 ; Tian et al., 2013a , b ; Li et al., 2015 ; Steiner et al., 2018 ) and the efficacy of dopamine antagonists in patients with schizophrenia ( Olgiati et al., 2009 ; Sagud et al., 2010 ; Huang et al., 2016 ). These previous findings converge to indicate that the reciprocal interactions between COMT genotype, dopamine levels, and structural and/or functional alterations in the human brain are related to mental disorder symptoms, such as AVHs ( Lu et al., 2007 ; Kang et al., 2010 ; Sagud et al., 2010 ; Gothelf et al., 2011 ; Edgar et al., 2012 ; Tian et al., 2013a , b ; Li et al., 2015 ; Huang et al., 2016 ; Steiner et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, COMT-Val/ Val homozygotes exhibit very efficient COMT activity, COMT-Met/Met homozygotes exhibit hypo-efficient COMT activity, and Val/Met heterozygotes carrying both variants of the enzyme exhibit an intermediate activity level, generally within normal range. COMT-Val158Met genotype (COMT genotype from here forward for simplicity) has also been shown to influence structural and functional aspects of auditory processing, including dopaminergic alterations in both healthy subjects and patients with schizophrenia (Edgar et al 2012;Gothelf et al 2011;Kang et al 2010;Li et al 2015;Lu et al 2007;Steiner et al 2018;Tian et al 2013a;Tian et al 2013b). Hence, a convergence of findings indicates that there may be reciprocal interactions between COMT genotype, dopamine levels, and structural/functional brain alterations in relation to neuropsychiatric symptoms, such as AVHs (Edgar et al 2012;Gothelf et al 2011;Huang et al 2016;Kang et al 2010;Li et al 2015;Lu et al 2007;Sagud et al 2010;Steiner et al 2018;Tian et al 2013a;Tian et al 2013b).…”
Section: Introductionmentioning
confidence: 99%